Factors affecting the concentration of financial services in the non metropolitan United States, 2000-2003 - Button, Ryan (Kansas State University, 2008)
Over the last twenty-five years, the environment for banking has changed radically. In the 1980s, legislation was enacted to permit both interstate branching and combinations of banks, securities firms, and insurance companies. A generally strong economy, as well as deregulation, led to marked improvements in bank profitability and capital positions. At the same time, however, the deregulation of products and markets intensified competition among banks and between banks and nonbank financial companies. This, combined with improved information technology, applications for banking, accelerated the consolidation of the banking industry through mergers and acquisitions and set the stage for the establishment of huge banking firms of unprecedented size and complexity. While processes such as mergers and acquisitions decreased the number of firms, competition between these firms prompted the growth of new establishments in banking and financial services. While a larger proportion of the literature has focused on the structural and regulatory changes among firms that have arose during this transformation, little attention has been given to the factors that affect the location of physical establishments. This is particularly the case in relation to the location of new banking establishments in the nonmetropolitan U.S. It is the intention of this thesis to come to a better understanding of the factors that affect the locations of these establishments, in hopes of adding more insight into the process of bank establishment growth.
Keywords: bank growth; industrial location; growth node; Sociology, General (0626)